Abnormal Cardiac Repolarization in Thyroid Diseases: Results of an Observational Study - Aweimer, Assem; Schiedat, Fabian; Schöne, Dominik; Landgrafe-Mende, Gabi; Bogossian, Harilaos; Mügge, Andreas; Patsalis, Polykarpos C.; Gotzmann, Michael; Akin, Ibrahim; El-Battrawy, Ibrahim; Dietrich, Johannes W. (Frontiers in Cardiovascular Medicine, 2021)
Background: The relationship between thyroid function and cardiac disease is complex. Both hypothyroidism and thyrotoxicosis can predispose to ventricular arrhythmia and other major adverse cardiovascular events (MACE), so that a U-shaped relationship between thyroid signaling and the incidence of MACE has been postulated. Moreover, recently published data suggest an association between thyroid hormone concentration and the risk of sudden cardiac death (SCD) even in euthyroid populations with high-normal FT4 levels. In this study, we investigated markers of repolarization in ECGs, as predictors of cardiovascular events, in patients with a spectrum of subclinical and overt thyroid dysfunction. Methods: Resting ECGs of 100 subjects, 90 patients (LV-EF > 45%) with thyroid disease (60 overt hyperthyroid, 11 overt hypothyroid and 19 L-T4-treated and biochemically euthyroid patients after thyroidectomy or with autoimmune thyroiditis) and 10 healthy volunteers were analyzed for Tp-e interval. The Tp-e interval was measured manually and was correlated to serum concentrations of thyroid stimulating hormone (TSH), free triiodothyronine (FT3) and thyroxine (FT4). Results: The Tp-e interval significantly correlated to log-transformed concentrations of TSH (Spearman's rho = 0.30, p < 0.01), FT4 (rho = −0.26, p < 0.05), and FT3 (rho = −0.23, p < 0.05) as well as log-transformed thyroid's secretory capacity (SPINA-GT, rho = −0.33, p < 0.01). Spearman's rho of correlations of JT interval to log-transformed TSH, FT4, FT3, and SPINA-GT were 0.51 (p < 1e−7), −0.45 (p < 1e−5), −0.55 (p < 1e−8), and −0.43 (p < 1e−4), respectively. In minimal multivariable regression models, markers of thyroid homeostasis correlated to heart rate, QT, Tp-e, and JT intervals. Group-wise evaluation in hypothyroid, euthyroid and hyperthyroid subjects revealed similar correlations in all three groups. Conclusion: We observed significant inverse correlations of Tp-e and JT intervals with FT4 and FT3 over the whole spectrum of thyroid function. Our data suggest a possible mechanism of SCD in hypothyroid state by prolongation of repolarization. We do not observe a U-shaped relationship, so that the mechanism of SCD in patients with high FT4 or hyperthyroidism seems not to be driven by abnormalities in repolarization.